1973
DOI: 10.1128/jb.113.1.38-41.1973
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Some Enterococci by Gas Chromatography

Abstract: Relative fatty acid compositions of 37 enterococci were examined by gas chromatography. Streptococcus faecalis, S. faecium, and S. faecium var. durans yielded similar fatty acid patterns. Strains of S. faecium var. casseliflavus, and a motile yellow-pigmented streptococcus, contained very low levels of C9:o0 on August 5, 2020 by guest

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…Andrewes, 1906 andElliot et al (1990) were reported the morphological characteristics of Streptococcus mitis are almost similar with the current study. Streptococcus salivarius showed the cultural and morphological characteristics were found closely similar with those that reported by Kathry et al (1984), Facklam et al (1977) and Amstein et al (1973). The cultural and morphological characteristics of Staphylococcus aureus recorded in this study is agreed with those that reported by Comolai et al (2008) and Hanselman et al (2009).…”
Section: Discussionsupporting
confidence: 91%
“…Andrewes, 1906 andElliot et al (1990) were reported the morphological characteristics of Streptococcus mitis are almost similar with the current study. Streptococcus salivarius showed the cultural and morphological characteristics were found closely similar with those that reported by Kathry et al (1984), Facklam et al (1977) and Amstein et al (1973). The cultural and morphological characteristics of Staphylococcus aureus recorded in this study is agreed with those that reported by Comolai et al (2008) and Hanselman et al (2009).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the di-unsaturated 18-carbon acid (18:2) was completely resolved from both oleic (18: 1; 9, 10) and cis-vaccenic (18:1, 11, 12) acids. Thus, in contrast to the results obtained with packed columns in earlier studies [5][6][7][8], use of the capillary column allowed for accurate quantitative determination of all of the fatty acid components of S. faecalis includin~ the positional isomers of unsaturated acids as shown in Table 1. Each of the five strains examined contained palmitic (16:0) and cis-vaccenic (18 : 1; A11) acid as the two major acids with small (1-4%) to moderate (5-13%) amounts of myristic (14:0) stearic (18 : 0), palmitoleic (16 : 1; A9), oleic (18: 1; A9), and lactobacillic (19 cyc; 11,12) acids.…”
Section: Resultsmentioning
confidence: 73%
“…In recent years, gas-liquid chromatography (GLC), mass spectrometry (MS), and associated analytical techniques have been used to study the chemical composition and metabolic activity of microorganisms as a basis for their classifications [1][2][3][4][5]. Chemical data such as cellular fatty acids have provided valuable information for the recognition of genus or species of various bacteria including streptococci [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations